SISTEM INFORMASI PENJUALAN DENGAN KONTROL TRANSAKSI SECARA ONLINE MENGGUNAKAN CODEIGNITER - Affandi, Luqman (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
Point Of Sale (POS) is a computer program that is used to assist the process of buying and selling goods. The program includes a warehouse transaction records, the process at the cashier and management report for the owner. The program is not limited to use in the store, but in a few places that provide public services and selling goods, such as pharmacies, clinics and more.In a small scale, POS program is usually run by the owner of the store itself or entrusted to one of its employees. Owners or employees of the store will input the name of goods, quantity of goods, managing stock, serving customers, and to make daily reports as well as income. If this is the case, then the owner will be able to control all activities of transactions.If the owners are not always at the store, then allow to happen fraud committed by employees, in order to avoid this it is necessary to control the transactions that occur in order to minimize the possibility of fraud by having each transaction will always be reported online via email owners, and also the final recap report daily transactions at the time of the transaction employee to log out of the system.Â Keywords : POS, online